Resource Use Efficiency in Rice Production, - B. Nirmala, (Journal of Agricultural Extension Management, 2025)
Rice is one of the staple food crops in India occupying 43 million hectares with a production of 93 million tones. It is estimated that about 260 million tones (MT) of food grains are to be produced annually by the year 2030 to meet the food requirements of the growing population (Reddy A R and Sen C. 2004). It is projected that India needs to produce 115 mt of rice by the year 2020 to maintain the present level of self-sufficiency. The available evidence suggests that farmers in developing countries fail to exploit the full potential of a technology and or make allocative errors